2016
DOI: 10.1016/j.intimp.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 plays a central regulatory role in the cytokines induced by hepatitis C virus core protein and polyinosinic acid:polycytodylic acid

Abstract: Hepatitis C virus (HCV) can cause persistent infection and chronic liver disease, and viral factors are involved in HCV persistence. HCV core protein, a highly conserved viral protein, not only elicits an immunoresponse, but it also regulates it. In addition, HCV core protein interacts with toll-like receptors (TLRs) on monocytes, inducing them to produce cytokines. Polyinosinic acid:polycytodylic acid (polyI:C) is a synthetic analogue of double-stranded RNA that binds to TLR3 and can induce secretion of type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…A study has suggested that chronic hepatitis C patients treated with recombined IL‐10 showed a reduction in fibrosis score, which revealed that IL‐10 is closely associated with the disease progression in CHC patients, and was consistent with our results. As is known, IL‐10 is an important anti‐inflammatory cytokine, IL‐10 may limit hepatic inflammation and injury, but it also contributes to the persistence of HCV virus . Tumor cells also could secret IL‐10 which induced the high serum IL‐10 level in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…A study has suggested that chronic hepatitis C patients treated with recombined IL‐10 showed a reduction in fibrosis score, which revealed that IL‐10 is closely associated with the disease progression in CHC patients, and was consistent with our results. As is known, IL‐10 is an important anti‐inflammatory cytokine, IL‐10 may limit hepatic inflammation and injury, but it also contributes to the persistence of HCV virus . Tumor cells also could secret IL‐10 which induced the high serum IL‐10 level in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Impact of HCV on cytokine production from monocytes: IL-10, an anti-inflammatory cytokine, can be produced by monocytes[ 74 ]. IL-10 has several immunoregulatory functions after HCV infection.…”
Section: Impact Of Hcv On the Mpsmentioning
confidence: 99%
“…In our lab, we studied the network of cytokines that regulate IL-10 production and the cytokines regulated by IL-10 upon HCV infection[ 74 ]. The stimulation of monocytes with HCVc and polyI:C induces the secretion of TNF-α, IL-1β, IL-10, and type I IFN.…”
Section: Impact Of Hcv On the Mpsmentioning
confidence: 99%
See 1 more Smart Citation
“…In chronic HCV infection, the functionality of both innate and adaptive immunity is affected. Monocytes are bone marrow-derived phagocytes involved in critical immune processes that convert innate immunity to adaptive to defend the host against pathogens (4,5). Our previous research study demonstrated that HCV inhibits IL-12 production and STAT-1 phosphorylation (p-STAT-1) in monocyte (M) through crosstalk between Tim-3 and PD-1 and SOCS-1 (6).…”
Section: Introductionmentioning
confidence: 99%